The cognitive profiles of pupils involved in sports activity - Hirynskaya, Anastasiya Yu. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article presents the results of the cognitive profiles of the individual students was included in sport activities. The motivational typological, formal-dynamic and psychomotor characteristics of the individual was dedicated. This individual is prone to making errors of attention, memory and actions. Based on the characteristics of the individual was built cognitive profiles corresponding to sensory, mnemonic and regulatory component of cognitive sphere, respectively: inattentional, oblivionis and omissional. The recommendations for prevention of erroneous actions of students in sport, in accordance with the predominance of a particular cognitive profile was involved in this article.